Prevalence of the ABCB1-1Δ gene mutation in a sample of New Zealand Huntaway dogs - Gedye K; Poole-Crowe E; Shepherd M; Wilding A; Parton K; Lopez-Villalobos N; Cave N (Informa UK Limited, trading as Taylor & Francis Group, 2023)
AIMS: To determine the prevalence of the ATP Binding Cassette Subfamily B Member 1-1Δ mutation (ABCB1-1Δ; previously Multidrug Resistance 1 (MDR1) mutation) in a cohort of New Zealand Huntaway dogs. MATERIALS AND METHODS: Samples were opportunistically collected from Huntaway dogs (n = 189) from throughout New Zealand. Buccal swabs were collected from 42 Huntaways from the Wairarapa region and 147 blood samples from Huntaways from the Gisborne, Waikato, Manawatū/Whanganui, Hawkes Bay, Canterbury and Otago regions. DNA was extracted from all samples and tested for the presence of the ABCB1-1Δ allele. RESULTS: Of 189 Huntaway dogs that were tested, two were found to be heterozygous carriers of the ABCB1-1Δ allele and the remaining 187/189 dogs were homozygous for the wild type allele. No dogs homozygous for the mutation were identified. CONCLUSIONS AND CLINICAL RELEVANCE: The results of this study show that the ABCB1-1Δ allele is present in Huntaway dogs. The low prevalence in this convenience sample suggests that the prevalence of this allele in the Huntaway population is likely to be low. We recommend that veterinary clinicians discuss the potential for this mutation in Huntaways with dog owners including the clinical implications for dogs that are homozygous for the mutated allele and the potential for testing for the mutation, as they would do for other known mutations.
Keywords: ABCB1-1Δ; Huntaway; dog; multiple drug resistance; prevalence; Animals; ATP Binding Cassette Transporter, Subfamily B, Member 1; Mutation; New Zealand; Prevalence; Cohort Studies; Working Dogs